Diálogos de professores: efeitos do Enem nos saberes e nas práticas docentes de História e de Língua Portuguesa do IFTM - Nascimento, Carla Alessandra de Oliveira (2020)
This investigation was carried out in the Graduate Program in Education at the Federal University of Uberlândia (PPGED / UFU), in the line of research Knowledge and Educational Practices. The study aimed to understand the effects of the National High School Examination (ENEM) on the knowledge and practices of high school History and Portuguese language teachers at the Federal Institute of Triângulo Mineiro (IFTM), inspired by the Policy Cycle Approach, developed by Ball and Bowe (1992). The study is inserted in the field of qualitative educational research approach, and the bibliographic review went through all the stages of conducting the realization of the research. The methodological option adopted was the case study, based on Stake (1983), Yin (2001), Ludke (1983), Alves-Mazzotti (2006) and André (2008; 2013). The data collection procedures were the questionnaire, the narrative interview - based on the theoretical methodological support of thematic oral history, according to Thompson (2002), Connelly and Clandinin (1995), Portelli (1996), Guimarães (1997), Joutard (2000 ), Meihy and Ribeiro (2011), Meihy and Holanda (2015), Jovchelovitch and Bauer (2015) - and the analysis of public documents. The data analysis had Bardin's Content Analysis (AC) as its theoretical-analytical reference (2011) and the documentary analysis, according to Cellard (2008). The research collaborators were 38 teachers from IFTM, from the disciplines History and Portuguese Language, to whom the questionnaire was applied. Among them, 16 were selected to carry out the narrative interviews. As effects of Enem, in this investigation, it was found that there were dislocations and ruptures in the conceptions that the collaborating teachers had about the Exam at different times. The record of displacement of the conceptions was greater than that of ruptures. The effects of Enem related to teachers' adhesion, resistance and difficulties in relation to Enem were identified as an instrument for evaluating high school graduates (in which the resistance of collaborating teachers prevailed) and as a way of accessing higher education (in which it prevailed adhesion, since Enem is associated with the quota policy). It was evident the effect of Enem on the knowledge and practices of teachers with regard to interdisciplinarity (History and Portuguese Language). It was found that the investigated have autonomy and opportunities in relation to Enem in the IFTM. However, this autonomy was not constituted without resistance, which occurred mainly in the coexistence between technical and propaedeutic teaching. The effects on the knowledge and practices of the investigated teachers occurred, mainly, due to the students' demand. The Enem influences the teachers' curricula and the teaching materials they use, but does not compose them exclusively, since other documents, such as the PPCs of the courses, also mark the curricula built in the classroom. Regarding the effects of Enem as a public education policy and its role in the composition of social justice, for the investigated teachers, the Exame contributes to social justice by bringing access to higher education to a more democratic process and by linking itself to other educational policy programs, such as Prouni and Fies.